Winter water - Jansson, Susanne (Grand Central Publishing, 2022)
"Martin, who has always been drawn to the ocean, moves his wife Alexandra and their two young children move to his family's idyllic summer cottage in the picturesque island village of Orust, on the west coast of Sweden. Martin begins to cultivate a mussel farm, where he soon runs into trouble with the locals. One January weekend, in the few moments Martin is distracted by a ringing phone, his young son goes missing, leaving his little red bucket bobbing in the waves. Though his body is never found, it's ruled an accidental drowning. Martin's grief is all-consuming as he falls into a deep depression, withdrawing from his family and community. When former police photographer Maya Linde arrives to Orust, she learns of the little boy's disappearance and decides to do some investigating of her own. Martin and Maya grow closer as they learn the hidden truths of this town and the locals who have always mythologized the ocean. Together they make a macabre discovery: other children have tragically died in the these waves, all on the same day in January, all in the exact same spot, though decades apart. Can it really be a coincidence, or is the ocean luring the children into its depths? As Maya and Martin grapple with a threat far greater than they ever imagined, they soon realize that the truth is actually much stranger than fiction... Set against a backdrop of the whispering, threatening ocean, Winter Water is an atmospheric and gripping suspense novel of the terrible things grief can make us capable of."--